1997
DOI: 10.1161/01.atv.17.3.528
|View full text |Cite
|
Sign up to set email alerts
|

7E3 Monoclonal Antibody Directed Against the Platelet Glycoprotein IIb/IIIa Cross-reacts With the Leukocyte Integrin Mac-1 and Blocks Adhesion to Fibrinogen and ICAM-1

Abstract: Recent clinical trials suggest that blockade of integrins is a promising strategy for the treatment of acute coronary syndromes. Administration of 7E3 monoclonal antibody (mAb) Fab fragment (c7E3 Fab) directed against platelet integrin IIb/IIIa (alpha IIb beta 3, CD41/CD61) reduces acute ischemic complications of coronary angioplasty and clinical restenosis at 6 months. However, 7E3 mAb is not selective for platelet IIb/IIIa but also cross-reacts with the leukocyte integrin Mac-1 (alpha M beta 2, CD11b/CD18) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
101
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(103 citation statements)
references
References 54 publications
1
101
0
1
Order By: Relevance
“…Given the long half‐life of inclacumab comparable to that of other human IgG antibodies and the persistent inhibition of platelet–leukocyte aggregates demonstrated after inclacumab administration,24, 25 alternative signaling cascades involving rapidly activated pathways and short‐term effects at maximum drug concentrations achieved at the end of the infusion may have accounted for these findings. Furthermore, cross‐reactivity of inclacumab with other receptors, similar to the observations reported for different drugs including glycoprotein IIb/IIIa antagonists,26, 27 may come into play. This raises the question of whether shorter (<1 hour) time intervals between study drug infusion and PCI or continuous infusions administered throughout the procedure, along with intracoronary infusion methods, would have caused an even larger effect.…”
Section: Discussionsupporting
confidence: 75%
“…Given the long half‐life of inclacumab comparable to that of other human IgG antibodies and the persistent inhibition of platelet–leukocyte aggregates demonstrated after inclacumab administration,24, 25 alternative signaling cascades involving rapidly activated pathways and short‐term effects at maximum drug concentrations achieved at the end of the infusion may have accounted for these findings. Furthermore, cross‐reactivity of inclacumab with other receptors, similar to the observations reported for different drugs including glycoprotein IIb/IIIa antagonists,26, 27 may come into play. This raises the question of whether shorter (<1 hour) time intervals between study drug infusion and PCI or continuous infusions administered throughout the procedure, along with intracoronary infusion methods, would have caused an even larger effect.…”
Section: Discussionsupporting
confidence: 75%
“…This effect could be mediated by Mac-1 binding of abciximab on the surface of monocytes, thereby preventing the adhesion of monocytes to ligands such as ICAM-1 displayed by VSMCs. 26 The effect of an anti-CD-18 -blocking antibody effect that was similar to that of abciximab on VSMC killing by M-CSF-activated macrophages supports the participation of the Mac-1 receptor in the process.…”
Section: Discussionmentioning
confidence: 76%
“…14,15 Abciximab also binds to the integrin ␣ V ␤ 3 16,17 and Mac-1 (␣M␤ 2 ) receptors. 18 The phase III Evaluation of IIb-IIIa platelet receptor antagonist 7E3 in Preventing Ischemic Complications (EPIC) study demonstrated that abciximab decreased acute ischemic events after PTCA by 35% and that it decreased restenosis 6 months after PTCA by 23%. 19 Ticlopidine has also been successful in reducing adverse cardiac events after PTCA with stent implantation.…”
mentioning
confidence: 99%